Peran LAZISNU terhadap Kesejahteraan Muallaf pada Masa Pandemi Covid-19 (Studi Kasus di Sorong Papua Barat) - Annisa Mangole (LABATILA : Jurnal Ilmu Ekonomi Islam, 2021)
This study aims to determine the role of LAZISNU in fostering the economy of converts to Sorong, West Papua through the distribution of zakat, infaq, and alms during the Covid-19 pandemic. The research approach used in this study is a descriptive qualitative approach using the case study method. The informants in this study consisted of LAZISNU Sorong management and Muallag administrators who received capital loans during the Covid-19 pandemic. Data collection was carried out by observation, interview and documentation techniques. The results showed that during the Covid-19 pandemic LAZISNU Sorong succeeded in prospering converts through an economic development program where the success of LAZISNU Sorong's economic development was measured by indicators of fulfilling basic needs, additional needs, education, health, economic security, social care and worship.